ANALYSIS OF LOCAL ORANGES COMPETITIVENESS AGAINST IMPORTED ORANGES: COMMUNITY PERCEPTIONS IN DKI JAKARTA - Fadhil Sitoda Syahadi; Osni Erza (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This study aims to analyze the competitiveness of local oranges fruits and imported oranges fruits: community perceptions in DKI Jakarta using the LISREL 8.80 and SPSS 25 processing tools, followed by a SWOT analysis. The variable used is a latent variable, namely the Competitiveness of Local Oranges against Imported oranges, Community Social Status, Quality of Oranges, and Price of Oranges. The data comes from surveys through questionnaires that are distributed to people in DKI Jakarta who consume local orange fruits and imported oranges fruits. The results of the study showed that the social status of respondents occupied in determining local orange fruit was 3.98% greater, compared to buying imported oranges was as much as 3.90%. , While buying imported oranges is 3.92. From the many opinions of respondents, the price of oranges in traditional markets is cheaper. Respondents choose local oranges at 3.94, compared to imported oranges are 3.79. Then the SWOT is its strength, namely that many people buy local oranges with recommendations from family, friends, and other people, and many people like the local oranges because the prices are very affordable, the weakness is that many of them still choose their imported oranges to buy. like, and also because the skin of the fruit is very beautiful and the sweetest. The opportunity is that local orange fruit traders have the opportunity to market their local oranges fruit as usual because many people want it, and the disadvantage is that some people still look at their orange peel because they think that when they see a good orange peel it means that the oranges are very sweet and fresh to consume, which is shown in imported oranges fruits.